Standardized surgical technique for single-port totally extraperitoneal inguinal hernia repair using the glove method with an intraumbilical incision - Yoshiro Imai; Yusuke Suzuki; Mitsuhiro Asakuma; Yoshiharu Miyamoto; Hideki Tomiyama; Sang-Woong Lee (PLoS ONE, 2025)
Background The safety of single-port totally extraperitoneal (STEP) inguinal hernia repair compared to conventional totally extraperitoneal (CTEP) has been supported by various randomized controlled trials (RCTs). However, the optimal method remains unclear because of variations in the location and length of the incision as well as different uses of the single-port device. We standardized STEP using the glove method with a straight umbilical incision that maintained the wound profile within the confines of the umbilicus for better cosmetic satisfaction and port operative pain reduction. Methods The incision length was limited to 1–1.5 cm, extending no further than the umbilicus. The STEP is performed utilizing the glove method using Alexis of XXS size. To minimize forceps interference, the surgeon dissected the spermatic cord into two distinct phases. As the mesh was inserted within the pneumoperitoneum, it was deployed safely and securely. In addition, we present the surgical outcomes at our institution for an early career surgeon. Results A total of 25 unilateral inguinal hernia STEP procedures were performed between April and October 2023. The median operative time was 68 minutes, and the procedure was performed safely with no complications requiring treatment. Conclusion In conclusion, STEP using the glove method with a total intraumbilical incision can be safely performed by an early career surgeon.